Stone Cladding Engineering - Sousa Camposinhos, Rui de.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume presents new methodologies for the design of dimension stone based on the concepts of structural design while preserving the excellence of stonemasonry practice in façade engineering. Straightforward formulae are provided for computing action on cladding, with special emphasis on the effect of seismic forces, including an extensive general methodology applied to non-structural elements. Based on the Load and Resistance Factor Design Format (LRDF), minimum slab thickness formulae are presented that take into consideration stress concentrations analysis based on the Finite Element Method (FEM) for the most commonly used modern anchorage systems. Calculation examples allow designers to solve several anchorage engineering problems in a detailed and objective manner, underlining the key parameters. The design of the anchorage metal parts, either in stainless steel or aluminum, is also presented.
Preface -- 1 Cladding with Stone: Introduction -- 2 Natural Stone Characterization -- 3 Wall and Cladding Systems -- 4 Limit States Design -- 5 Actions and Stone Strength -- 6 Dowel Anchorage -- 7 Undercut Anchorage -- 8 Kerf Anchorage -- 9 Stainless Steel and Aluminium Anchors -- Index.
Keywords: Engineering; Mechanical engineering; Civil engineering; Materials; Engineering; Civil Engineering; Structural Materials; Structural Mechanics